Developing collaborative strategies to address challenges and leverage opportunities in traditional arts digital preservation - Rafianti, Laina; Khadijah, Ute Lies Siti; Sarilita, Erli; Martina, Martina; Juliandri, Arfan (Jurnal Informatio, 2026)
Background: The rapid advancement of digital technologies has transformed how cultural heritage is preserved, accessed, and disseminated. While digitalization offers new opportunities to revitalize traditional arts and engage younger generations, it raises concerns related to cultural authenticity, technical capacity, and ethical governance.Purpose: This study examines (1) how digital technologies contribute to the preservation and revitalization of traditional arts, (2) the key challenges faced by artists and cultural practitioners in adapting to digital environments, and (3) the collaborative strategies required to ensure culturally grounded and sustainable digitalization. Methods: A qualitative approach was employed using semi-structured interviews with five informants, including traditional artists, academics, and cultural practitioners involved in heritage-related activities in Indonesia. Data were analyzed thematically to identify recurring patterns related to digital preservation practices, challenges, and forms of collaboration.Results: Findings show that digitalization strengthens preservation by expanding accessibility, protecting fragile archives, and creating immersive experiences through technologies such as virtual reality and digital platforms. However, informants highlight significant constraints, including digital literacy gaps, inadequate infrastructure, financial barriers, and intellectual property risks. They emphasize that authentic cultural values must remain central in digital transformation. Effective digitalization requires multi-stakeholder collaboration—linking artists, communities, academics, government, and technology actors to ensure accuracy, cultural integrity, and sustainable implementation. Conclusions: Digital technologies hold meaningful potential for revitalizing traditional arts when applied ethically and collaboratively. Sustainable digital preservation requires culturally sensitive approaches, institutional support, and coordinated multi-stakeholder engagement. Future research should involve broader participant groups and comparative cultural contexts to deepen understanding of long-term digital preservation strategies.